Induced HBs antigenemia in healthy adults after immunization with two different hepatitis B recombinant vaccines - Ziaee, Masoud; Saádatjoo, Alireza; Mohamadpour, Malihe; Namaei, Mohammad Hasan (Hepatitis monthly, 2010)
Currently, vaccination is the most effective protective tool against hepatitis B virus infection. Some studies have shown that positive results for a hepatitis B virus surface antigen (HBsAg) test may be seen after vaccination. In this clinical trial study, 62 healthy adult volunteers were randomly assigned to receive either the Engerix-B or the Hepavax-Gene hepatitis B recombinant vaccine. Blood samples were drawn 1, 3, and 5 days after vaccination and were tested for HBsAg using two different ELISA kits (Behring and Mega). HBsAg was positive in 5, 3, and 2 participants of the Engerix-B group in the 1st, 3rd, and 5th days after vaccination, respectively, using the Behring ELISA kit the test was positive in only one subject in the Hepavax-Gene group, on the 5th day after vaccination. No positive result was seen in any groups when the Mega ELISA kit was used to test the specimens. Our results showed transient HBsAg antigenemia after vaccination against hepatitis B. This condition depends on the type of vaccine and the HBsAg diagnostic test.